Early head‐to‐pelvis computed tomography in out‐of‐hospital circulatory arrest without obvious etiology. (24th March 2021) - Branch, Kelley R. H.; Strote, Jared; Gunn, Martin; Maynard, Charles; Kudenchuk, Peter J.; Brusen, Robin; Petek, Bradley J.; Sayre, Michael R.; Edwards, Rachael; Carlbom, David; Counts, Catherine R.; Probstfield, Jeffrey L.; et al.
Abstract: Objectives: Patients resuscitated from an out‐of‐hospital circulatory arrest (OHCA) commonly present without an obvious etiology. We assessed the diagnostic capability and safety of early head‐to‐pelvis computed tomography (CT) imaging in such patients. Methods: From November 2015 to February 2018, we enrolled 104 patients resuscitated from OHCA without obvious cause (idiopathic OHCA) to an early sudden‐death CT (SDCT) scan protocol within 6 h of hospital arrival. The SDCT protocol included a noncontrast CT head, an electrocardiogram‐gated cardiac and thoracic CT angiogram, and a nongated venous‐phase abdominopelvic CT angiogram. Patients needing urgent cardiac catheterization or hemodynamically unable to tolerate SDCT were excluded. Cardiac CT analyses were blinded, but other SDCT findings were clinically available. Primary endpoints were the number of OHCA causes identified by SDCT compared to the adjudicated cause and critical diagnoses identified by SDCT, including resuscitation complications. Safety endpoints were acute kidney injury (AKI) and inappropriate treatments based on SDCT findings. Acute coronary syndrome was the presumed etiology if any major coronary artery had a >50% stenosis without another OHCA cause. Results: SDCT scans occurred within 1.9 ± 1.0 h of hospital arrival and identified 39% (41/104) of all OHCA causes and 95% (39/41) of causes potentially identifiable by SDCT. Critical findings were identified by SDCT in 98% (43/44) of patients that included potentially life‐threatening resuscitation complications of liver or spleen laceration ( n = 6); pneumothorax or thoracic organ laceration ( n = 8); and mediastinal, pericardial, or vascular hemorrhage ( n = 3). SDCT exclusively identified 13 (13%) OHCA causes that would otherwise not be identified without SDCT imaging. No inappropriate treatments resulted from SDCT findings. AKI was common (28%) but only one (1%) patient required new dialysis. Conclusions: This observational cohort study suggests that early SDCT scanning is safe, can expedite the diagnosis of potential causes, and can meaningfully change clinical management after idiopathic OHCA.